Diseño e implementación de un cuarto de telecomunicaciones para la empresa Puntonet S.A. ubicado en la zona norte de Quito - Castro Rosero, Damián Fabricio (2014)
This research study is based on obtaining a suitable design of the telecommunications room to be implemented in the “Zabala” node of Puntonet S.A. The same that is located in the Zabala neighbor at northern of Quito city. The telecommunications room shall comply with all currently parameters and standards. The research has been structured into 5 chapters: Chapter I is the introduction of the topic, in which the reason for the research is justified. In Chapter II, the literature method will be used in order to obtain the information that theoretically will be based in the design of the telecommunications room to be implemented in the “Zabala” node….